Human impact: Ecological footprints - Maric, Filip; Poto, Margherita Paola; Panieri, Giuliana; Peftieva, Olena (Septentrio Educational, 2023)
Focus: To understand the meaning of the human ecological footprint. Pupils will think about questions like how do our actions (e.g., research) affect the environment around us and, what can we do to reduce the human impact on the oceans? Learning objectives: In this activity, pupils will learn to develop an understanding of their relationship with the oceans and the marine environment and hopefully be inspired to turn their knowledge into action. Key words: Human impact, footprints, action.